Co-existence of cerebral cysticercosis with Japanese encephalitis: a prognostic modulator. - Desai, A. (Cambridge University Press, 1997)
In this study, we investigated the frequency of co-existence of cerebral cysticercosis (CC) in Japanese encephalitis (JE) cases with special emphasis on its role in predicting the final clinical outcome. Amongst the 163 confirmed cases of JE, 37.42% (61/163) had co-existent CC. This was confirmed by antibody detection in the CSF of 45 cases, CT scan of the brain in 6 cases and at autopsy in 3 cases. In 2 cases confirmation was possible by CT scan as well as at autopsy, in 4, CSF antibody levels and CT scan were suggestive of CC while in 1, CSF antibodies and autopsy were suggestive of CC The co-occurrence of Cysticercus cellulosae in the brain emerged as a prognosticator of poor outcome in JE cases (P < 0.03).